2006
DOI: 10.1159/000096459
|View full text |Cite
|
Sign up to set email alerts
|

RamA, the Transcriptional Regulator of Acetate Metabolism in <i>Corynebacterium glutamicum</i>, Is Subject to Negative Autoregulation

Abstract: The RamA protein represents a LuxR-type transcriptional activator of genes involved in acetate metabolism of Corynebacterium glutamicum. Here we analyze the expression of the respective ramA gene and its regulation. Transcription was found to start 71 nucleotides upstream of the translational start codon and to be two- to threefold up-regulated in the presence of acetate in the growth medium. Accordingly, about twofold higher amounts of RamA were observed in C. glutamicum cells grown on acetate instead of gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 42 publications
4
29
0
Order By: Relevance
“…The promoter activities in the cells cultured for 8 h (in the stationary phase) are summarized in Table 2. The activity of the wild-type promoter was higher in the cells grown on acetate than those grown on glucose (Table 2), which is consistent with previous results (43). The promoter carrying the above-described mutations in the GlxR binding site showed no detectable activity during growth under these conditions (Table 2), suggesting that GlxR plays an essential role in ramA expression.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The promoter activities in the cells cultured for 8 h (in the stationary phase) are summarized in Table 2. The activity of the wild-type promoter was higher in the cells grown on acetate than those grown on glucose (Table 2), which is consistent with previous results (43). The promoter carrying the above-described mutations in the GlxR binding site showed no detectable activity during growth under these conditions (Table 2), suggesting that GlxR plays an essential role in ramA expression.…”
Section: Resultssupporting
confidence: 90%
“…It has been reported that four transcription regulators, RamA, SugR, GlxR, and RamB, bind to the ramA promoter in vitro and/or in vivo (15,35,43). RamA is subject to negative autoregulation, as described above.…”
mentioning
confidence: 83%
See 3 more Smart Citations